The Role of Information and Documentation Management Officers (PPID) in Public Information Services at the Minahasa Regency Communication and Informatics Office - Wowor, Recky; Wawointana, Thelma; Mamonto, Fitri (JUPE : Jurnal Pendidikan Mandala, 2023)
Openness of public information has an important role as a manifestation of a democratic state which gives priority to people's sovereignty in monitoring the implementation of the duties of the state and other public bodies, as regulated in Law Number 14 of 2008. Public Information Management Officers (PPID) are responsible as officers who authorized to carry out public information provision services. The aim of this research is to assess the extent of the contribution of Information and Documentation Management Officers (PPID) in providing public information services in Minahasa Regency. The research method used in this study is a qualitative method, with data collection techniques through direct interviews with informants who are Information and Documentation Management Officers (PPID). The research results show that PPID's role in realizing public information openness in Minahasa Regency is in accordance with the provisions of Law Number 14 of 2008 and Minahasa Regent Regulation number 251 of 2015 concerning Management of Information and Documentation Services within the Minahasa Regency Government. However, there are several obstacles in implementation, both technical and non-technical. As a result of this research, it is recommended that Minahasa Regency consider adding staff or human resources in the IT sector, providing a special room for activities and data storage for Assistant PPIDs, and creating a data bank that has been validated by the relevant Regional Apparatus Organization (OPD) officials. . This is expected to increase the accessibility of public information for the community and facilitate the process of accessing information.